Genetic variants in RNA m5C modification genes associated with survival and chemotherapy efficacy of colorectal cancer. (21st July 2022) - Chen, Silu; Cao, Xiangming; Ben, Shuai; Zhu, Lingjun; Gu, Dongying; Wu, Yuan; Li, Shuwei; Yu, Qiang
Abstract: Background: Colorectal cancer is one of the most common malignant digestive tract tumors with a poor prognosis. RNA 5‐methylcytosine (m 5 C) is an important posttranscriptional widespread modification involved in many biological processes. However, the association between genetic variations of m 5 C modification genes and the prognostic value of colorectal cancer remains unclear. Methods: We investigated the association between candidate single nucleotide polymorphisms (SNPs) in 13 m 5 C modification genes and colorectal cancer overall survival (OS) after chemotherapy by the Cox regression model. The combined effect of selected SNPs on OS, progression‐free survival (PFS), and disease control rate (DCR) was assessed by the number of risk alleles (NRA). The GTEx and TCGA database were used to perform expression qualitative trait locus (eQTL) analysis. Results: We identified that two SNPs in YBX1 were associated with OS after chemotherapy (HR = 1.43, p = 0.001 for rs10890208; HR = 1.36, p = 0.025 for rs3862218). A striking dose–response effect between NRA and OS after chemotherapy was found ( p trend = 0.002). The DCR of patients receiving oxaliplatin chemotherapy in the 3–4 NRA group was markedly reduced in comparison to that in the 0–2 NRA group (OR = 1.49, p = 0.036). Moreover, YBX1 mRNA expression was significantly overexpressed in tumor tissues ( p < 0.05) in the TCGA database, and eQTL analysis demonstrated that the two SNPs were associated with YBX1 ( p = 0.003 for rs10890208 and p = 0.024 for rs3862218). Conclusion: Our study indicates that genetic variants in m 5 C modification genes may mediate changes in YBX1 mRNA levels and affect the chemotherapeutic efficacy of colorectal cancer patients. Abstract : We identified that rs10890208 and rs3862218 in YBX1 were associated with colorectal cancer overall survival after chemotherapy. Our study indicates that genetic variants in m 5 C modification genes may mediate changes in YBX1 mRNA levels and affect the chemotherapeutic efficacy of colorectal cancer patients.